PENGIMPLEMENTASIAN APLIKASI GTK DALAM MENINGKATKAN KUALITAS TENAGA KEPENDIDIKAN DI SEKOLAH DASAR NEGERI PERCOBAAN PALANGKARAYA - Munawarah, Rizka; Dakir, Dakir; Irawan, Rio (Jurnal Manajemen Pendidikan, 2025)
The development of information technology has brought significant changes to the educational administration system, including the management of teacher and staff data in schools. The government introduced the GTK application as a digital tool to support data accuracy, effective personnel management, and the improvement of professional competence among educational staffThis study aims to analyze the implementation of the GTK application in improving the quality of educational staff at SD Negeri Percobaan Palangka Raya. The research employs a qualitative approach with a case study method to gain an in-depth understanding of the GTK application usage process among educational staff. The purposive sample consisted of 44 participants, including the principal, school operators, administrative staff, and teachers who actively use the GTK application. Data were collected through direct observation, in-depth interviews, and school administrative documentation, and analyzed qualitatively through data reduction, narrative presentation, and conclusion drawing. The results indicate that the GTK application significantly enhances administrative efficiency, improves the accuracy of teacher and staff data, and supports professional development for teachers. Key supporting factors include staff digital literacy, principal support, and adequate technological infrastructure, while obstacles include limited digital literacy among new teachers and uneven infrastructure availability.